Pengaruh Korean Celebrity Endorsement terhadap Persepsi Kualitas, Brand Image, dan Intensi Pembelian Merek Skincare Lokal - Lasse, Gabriela Junisa; Elizabeth, Michelle; Soehadi, Agus W.; Sirad, Dini Anggraeni (Universitas Prasetiya Mulya, 2024)
The extensive use of celebrity endorsements to the business competition is an interesting marketing phenomenon to be explored further. This study aims to examine the influence of Korean celebrity endorsement on brand image, perceived quality, and purchase intention of skincare brands in Indonesia, using the case study of Scarlett and their Korean celebrity endorsers, TWICE. Using a quantitative research method, a total of 200 respondent data were analyzed using SEM in the AMOS 26 program. The results showed that Korean celebrity endorsement, characterized by attractiveness, trustworthiness, and familiarity dimensions, had a positive and significant impact on brand image and perceived quality, ultimately leading to increased consumer purchase intention. This study also discusses the theoretical implications and practical implications that can be utilized by future researchers and business practitioners.